PROSPECTIVE INDONESIAN EFL TEACHERS’ PROBLEMS IN PLACING VERB STRESS - Lucia Niken Tyas Utami; Made Frida Yulia (ELTR Journal, 2022)
In creating successful communication, pronunciation is one aspect which should be mastered well by EFL learners, particularly by prospective teachers who will later become role models for their students. One of the essential pronunciation features is stress. Although sometimes neglected, stress is said to have necessary implication for one’s speaking skills. This study attempted to reveal the problems in verb stress placement encountered by prospective Indonesian EFL teachers. The data were obtained from the recording of their class presentations. The verbs uttered during the presentations were categorized into verb types depending on the number of syllables, i.e. disyllabic verbs, trisyllabic verbs, and tetrasyllabic (or longer) verbs, and then analyzed in terms of their pronunciation accuracy. From the analysis, it could be concluded that there were two kinds of problems in placing verb stress which the prospective Indonesian EFL teachers encountered, namely they misplaced the stress and they put double stresses on a verb. Most of them put the stress on syllables which could not obtain any stresses, such as suffixes. Meanwhile, some others put double stresses on either trisyllabic verbs or verbs with four or more syllables, where, in fact, such stresses could only be obtained by disyllabic verbs.